A Review on Experimental Investigation of Mechanical Properties of Coffee Husk Ash Concrete (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Aggregates and binders are the two main components of concrete. Cement is an ecologically unsociable process since it releases CO2 gas into the air and causes ecological deterioration; it is also the most expensive and environmentally unfriendly component of concrete. To help promote environmentally friendly building methods, this research looks at the possibility of using coffee husk ash (CHA) in place of certain traditional Portland cement in concrete mixes. Because of its possible environmental advantages and resource saving, the use of agricultural waste, such coffee husk ash, as an additional cementitious ingredient has attracted interest. This study makes use of controlled laboratory trials to determine how different concentrations of CHA affect the mechanical, durability, and workability characteristics of concrete. The concrete's structural performance is evaluated by testing its compressive strength, flexural strength, and split tensile strength. Initial findings suggest that CHA, when used in part as a cement substitute, might enhance workability and maybe even certain mechanical qualities. The trade-offs between improving sustainability and preserving structural integrity must be carefully considered. By investigating the feasibility of using coffee husk ash as an additive in concrete, this study adds important new information to the continuing efforts towards sustainable building practices. In an effort to create infrastructure that is less harmful to the environment, the results should guide practices in the concrete sector and encourage greener options.